Antioxidant and mineral studies in different genotypes of Indian bathua (Chenopodium album) - YADAV, R K; TOMAR, B S; PACHAURI, NEETU; BRIHMADEV, BRIHMADEV; JAIN, VARSHA (The Indian Journal of Agricultural Sciences, 2017)
Twelve genotypes of bathua (Chenopodium album L.) were evaluated for their yield and important mineral content, viz. iron, zinc, calcium, sodium, potassium, manganese and magnesium alongwith quality traits namely, total carotenoids, Î²-carotene, ascorbic acid, total phenolic content, Cuprac Ion Reducing Antioxidant Capacity (CUPRAC) and Ferric Reducing Antioxidant Power (FRAP). Leaf yield per ha was recorded maximum in Bathua Sel-2 (333q/ha) followed by Pusa Bathua-1 (300 q/ha), while Desi Bathua (local weed type) recorded lowest leaf yield of 65.1 q/ha. Considerable variability was recorded in total carotenoids which ranged from 32.39 mg/100 g (Bathua-6) to 89.2 mg/100 g (Bathua-7). Bathua-3 recorded maximum value of ascorbic acid (89.5 mg/100g) which was significantly higher than other genotype. High variability was recorded in total phenolic content, which ranged from 270.87 Î¼g gallic acid equivalent (GAE)/g (Bathua-6) to 820.47 Î¼g GAE/g (Bathua Sel-8). Antioxidant activities recorded by both CUPRAC and FRAP method was found high in Desi Bathua followed by Pusa Bathua-1. However, BathuaSel-7 was found rich source of carotene Î²-carrotene i.e. 89.24 and 10.80 mg/100g respectively. Desirable sodium to potassium ratio (